A heat waste recovery system via thermoelectric generator - Chai-Phing Chen; Siaw-Paw Koh; Sieh-Kiong Tiong; Jian-Ding Tan; Albert Yu-Chooi Fong (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Be it in the power production or consumption end, improvement on the power efficiency has become one of the most pivoting research topics over the past few decades. In order to reduce the reliance on fossil fuels and negative impacts on the environment, many ways are found to show promising results to increase power efficiency. One of the most effective ways is to recover and reuse heat waste. In this research, a heat waste recovery system is proposed by using thermoelectric generators (TEGs). This proposed heat recovery system can be implemented at the exhaust or the chiller section of a power system to abstract the excessive and unwanted heat and reuse it before it dissipates into the environment or goes to waste. Experiments are setup and conducted with controlled heat levels to investigate the performance of the proposed system in converting heat waste into electricity under different temperatures. The results show that the generated power hikes as the heat set-points increase from 30°C to 240°C. The output power fluctuates and shows no significant increase as the temperature increases from 240°C onwards. The maximum power is generated at 290°C. It can thus be concluded that the proposed system successfully generates electricity under different level of heat waste temperature. In time to come, this research can further explore the possibility on the optimization of the generated power.